THE SOCIAL MOBILITY OF POOR ITALIAN IMMIGRANT IN BRAZIL (1890-1930): A CONTRIBUTION TO THE HISTORIOGRAPHY IMMIGRATION IN SAO PAULO - Brandao, Marco Antonio (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias Humanas & Sociais, 2015)
This article presents a somewhat different analysis about what is commonly written about the relationship between Italian Immigration and industrialization in Brazil. The elucidation of this relationship often was confined to the phenomenon that occurred in the city of Sao Paulo, between 1880 to 1930. Contrary to what happened in the state capital, we show that the poor immigrant was not just that loser, expelled from the countryside, which to survive worked in some factory (often owned by a wealthy patrician). A little distant this scenario, approximately 300 kilometers from Sao Paulo city, Italian without resources, but holders of some know-how had a social mobility and helped constitute the industrial business in the city of Ribeirao Preto.
Keywords: Italian Immigration; Industrialization; social mobility; Nucleo Colonial Antonio Prado; Ribeirao Preto